Influence Of Dentist Gender And Clinical Experience On The Selection Of Posterior Restorative Dental Material: A Preliminary Study - Mohammad, Norazlina; Asy Abdul Aziz, Abdul Azim; Ahmad, Aimi Amalina; Jaafar, Azlan; Al-Kadhim, Aws H Ali (IIUM Medical Journal Malaysia, 2017)
Introduction: Dentist-related factors are one of the major influences on the material selection for restoration of carious and non-carious tooth surface loss. There were conflicting results regarding the impact of dentists’ gender and age or length of clinical experience on restorative material selection for posterior dentition. The aims of this study were to determine the influence of gender and clinical experience on posterior restorative material selection among private dental practitioner in Malaysia. Materials and Methods: This is a cross sectional study, and a selfadministered questionnaire was distributed randomly using a simple random method, among general private dental practitioner in Kuala LUMPur. Data gathered then analysed using SPSS version 21.0 and alpha error was set at p10 years working experience) were inclined to choose tooth coloured restorative material over amalgam at 87% and 83.9% respectively. Chi square test revealed non-significant difference in the material selection with relation to gender (p=0.852) and clinical experience (p=0.748). Conclusion(s): The dental practitioner’s gender and clinical experience in this study has no influence on the material selection for posterior restorations.